Empiricalization in the modern theory of argumentation: historical preconditions and areas of research - Khomenko Ірина (Actual Problems of Mind, 2022)
We can see various types of research in the modern theory of argumentation. Recently, scholars in this field have been actively discussing a new trend, namely, empiricalization. The paper is devoted to considering the historical preconditions for the emergence of this trend and clarifying its essence under modern conditions. The author justifies the point of view that the preconditions for empiricalization are two concepts developed at the end of the 1950s, namely: the concept of working logic by Stephen Toulmin and the concept of new rhetoric by Chaim Perelman and Lucy Olbrechts-Tyteka. In the author’s opinion, the foundations of modern empiricalization are based on their proposals for scholars (1) to study argumentation in a specific institutional context and (2) to analyze original texts from the history of various disciplines, in which the author’s position on a certain issue is argued. The article shows that the modern term "empiricalization" precisely corresponds to the growth of research on argumentative processes in various fields and contexts, namely in the history of science (scientific discussions and controversies), philosophy, legal context, medicine and health care, education, politics, culture, communication of people in everyday life and others. For that, scholars successfully use terminology and methodological tools developed within various theoretical approaches to argumentation, specifying them to certain empirical databases. To demonstrate this position, the following approaches and concepts are considered in detail in the paper: historical-textual and meta-argumentative concepts, which are based on the ideas and tools of informal logic; modern studies of argumentation in the field of medicine and health care within a pragma-dialectical approach and cross-cultural studies based on a psychological approach to interpersonal communication.